Lie algebra for rotational subsystems of a driven asymmetric top - Pozzoli, Eugenio; Leibscher, Monika; Sigalotti, Mario; Boscain, U.; Koch, Christiane P. (Journal of Physics A: Mathematical and Theoretical, 2022)
We present an analytical approach to construct the Lie algebra of finite-dimensional subsystems of the driven asymmetric top rotor. Each rotational level is degenerate due to the isotropy of space, and the degeneracy increases with rotational excitation. For a given rotational excitation, we determine the nested commutators between drift and drive Hamiltonians using a graph representation. We then generate the Lie algebra for subsystems with arbitrary rotational excitation using an inductive argument.
CRIS-Team Scopus Importer:2023-04-20
Keywords: controllability; Lie algebra; molecular rotation